Dynamic-statistical description of capture cross-section - initial stage of the fusion of heavy nuclei reaction - Anokhin, R.A.; Pavlii, K.V. (Вопросы атомной науки и техники, 2011)
To describe the capture cross-section (σc) and the initial stage of the formation of super-heavy elements dynamic- statistical model was proposed, it considers the nuclei interaction from contact time until the formation of the dinuclear system.Were made analysis of the nucleus-nucleus potential and shown that there exists a limitation of the angular momentum contributing to the capture cross-section, which is determined by the disappearance of a potential pocket. Dynamic examination allowed to reveal the main contribution of angular momentum in the capture cross- section. Were made analysis of the capture cross sections and dynamic characteristics of the reactions A²Fe + ²⁴⁴Pu and A²Ni + ²³⁸U from the beam kinetic energy.